The properties of styrene butadiene rubber/recycled chloroprene rubber (SBR/CRr) blends - Ahmad Azrem, Azmi
The effects of cure characteristics, physical and mechanical properties and morphological properties on styrene butadiene rubber/recycled chloroprene rubber (SBR/CRr) blends were investigated. SBR/CRr blends with blend ratios 95/5, 85/15, 75/25, 65/35 and 50/50 were prepared using two roll mill at room temperature and followed by compression moulding. The results on comparison of styrene butadiene rubber/virgin chloroprene rubber (SBR/CRv) blends with SBR/CRr blends showed that at similar blend ratios, particularly up to 15 phr, SBR/CRr blends exhibited improvement in tensile strength while the M100, hardness and crosslink density of SBR/CRr blends exhibited increment value in all blend ratios. The smallest size of CRr particles S1 (346-486 μm) in SBR/CRr blends showed a better cure characteristics and mechanical properties compared with all other blend ratios in S2 (664-891 μm) and S3 (0.3-0.7 mm). Futhermore, the processing become more efficient and the contact surface area increased which provided more efficient interfacial bonds. The compatibilization of SBR/CRr blends with 5 phr of trans-polyoctylene rubber (TOR) improved the adhesion between CRr and the SBR matrix, thus, improving the compatibility of SBR/CRr blends. Cure characteristics of compatibilised SBR/CRr blend have shorter scorch time, t2 and cure time, t90 than uncompatibilised SBR/CRr blends. Compatibilised SBR/CRr blends showed lower minimum torque (ML) compared to uncompatibilised SBR/CRr blends at all blend ratios. However, maximum torque (MH) of compatibilised SBR/CRr blends exhibit the opposite trend compared with the uncompatibilised SBR/CRr blends. The tensile strength, M100, hardness and crosslink density of compatibilised SBR/CRr blends also improved compared with uncompatibilised SBR/CRr blends. The cure time, t90 of SBR/CRr/CB blends and SBR/CRr/CaCO3 blends decreased with increasing CRr content in both blends. However, scorch time, t2, increased with increasing CRr content in both blends. SBR/CRr/CB blends showed higher minimum torque (ML) compared to SBR/CRr/CaCO3 blends at all blend ratios. However, maximum torque (MH) of SBR/CRr/CB blends exhibit the opposite trend compared with the SBR/CRr/CaCO3 blends. SBR/CRr/CB blends exhibited a better result in all mechanical and physical properties compared with SBR/CRr/CaCO3 blends at all blend ratios.